Estudos estruturais em órgãos reprodutivos de Tapirira guianensis Aubl. (Anacardiaceae) - Tölke, Elisabeth Emília Augusta Dantas, 1984- (2013)
Orientadores: Sandra Maria Carmello Guerreiro, Silvia Rodrigues Machado